FAMILY PLANNING COUNSELING BY VASECTOMY MOTIVATORS (CASE STUDY OF VASECTOMY COUNSELING COMMUNICATION BY MOTIVATORS IN SIATAS BARITA SUBDISTRICT, NORTH TAPANULI REGENCY) - Simbolon, Wanti Isadora Br.; Mazdalifah, Mazdalifah; Khairifa, Feni (International Journal of Social Service and Research, 2024)
This study aims to analyze counseling communication, obstacles faced, and efforts made by vasectomy motivators to prospective acceptors in Siatas Barita District, North Tapanuli Regency, Indonesia. The researcher used several data collection techniques to conduct this study, namely in-depth interviews and observations. The results of this study show that the motivators in the district have met the requirements as effective communicators in counseling. The motivational approach proposed by motivators shows the need for greater encouragement for men to take an active role in Family Planning (KB) programs. Efforts to increase promotion and information related to male family planning through social media, newspapers, and other information sources are important steps that are expected to increase the acceptance and participation of men in family planning programs, so that families can choose the family planning method that best suits their needs.